(untitled) (Altre Modernità, 2022)
In the past two years, the pandemic has forced teachers and students to adapt to a new form of distance teaching, also at university level. This article is based on the author’s direct experience at the School of Economics of the University of Milan-Bicocca, where English is the first compulsory language, while German is offered as an alternative to French and Spanish. Teaching a subject such as a language, in which communication is an essential part, is more challenging in online platforms. Since the participants (both teachers and learners) remain physically distant from each other, the online classroom context imposes strong limitations–which are not present in the face-to-face environment–on interaction. Examples of common problems encountered in eighteen months of remote teaching–and attempted solutions–are examined. The analysis of critical aspects and positive elements that emerged from this experience prompts reflection on some basic concepts of autonomous learning and the role of teachers and learners. The objective of this article is to examine the ways in which these concepts can be integrated into the institutional environment of the university, and to outline proposals for the study of German in both contexts, distance-learning and face-to-face, after returning (perhaps only partially) to the real classroom.